PENETAPAN UKURAN SASARAN PADA LIMA UNIT PENGGERGAIIAN KAYU JATI DI JAWA TENGAH & JAWA TIMUR - Osly Rachman; Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 1991)
Three teak wood sawmilis  in Central Java and two in East  Java have been selected for study on target aize determi- nation Using 100  board samples  from   each sawmill. The result was calculated using formulos for determining lumber tar get sizeThe  rasult  indicates that actual size produced by three sawmills were higher than target size,  ranging from 0.32 mm to 2.11  mm. The actual size produced by  two other sawmills was lower than the tagret size, ranging from 0.61  mm to 6.48 mnt 5.48 mm.  This result indicates  that target size determination is important  to improve  sawing  efficiency.